2007
DOI: 10.1021/ja070712q
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Tautomeric Equilibrium of 4-Hydroxypyrimidine with Its Ketonic Forms:  A Free Jet Millimeterwave Spectroscopy Study

Abstract: 4-Hydroxypyrimidine (4HP) has two conformational forms (the hydroxyl hydrogen cis or trans with respect to the adjacent nitrogen), which are in tautomeric equilibrium with two ketonic forms, 4-pyrimidinone (4PO) and 6-pyrimidinone (6PO). We have investigated the free jet absorption millimeterwave spectrum of this system, assigning the rotational spectra of 4HPcis and 4PO; the latter species is more stable by 2.0(9) kJ/mol. No lines corresponding to the trans isomer of 4-hydroxypyridine and to 6PO have been obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 26 publications
3
39
0
1
Order By: Relevance
“…The relative stabilities of three tautomers of 4PMO, as in Scheme , was previously predicted to be 3(H) (I) > hydroxy (II) > 1(H) (III) at the B3LYP/6‐31G++G(d,p) level of theory . Our B3LYP/6‐311++G(d, 2p) calculations indicate that in vacuum 3(H) (I) is 7.5 kJ·mol −1 more stable than hydroxyl (II), while hydroxyl (II) is 32.5 kJ·mol −1 more stable than 1(H) (III).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The relative stabilities of three tautomers of 4PMO, as in Scheme , was previously predicted to be 3(H) (I) > hydroxy (II) > 1(H) (III) at the B3LYP/6‐31G++G(d,p) level of theory . Our B3LYP/6‐311++G(d, 2p) calculations indicate that in vacuum 3(H) (I) is 7.5 kJ·mol −1 more stable than hydroxyl (II), while hydroxyl (II) is 32.5 kJ·mol −1 more stable than 1(H) (III).…”
Section: Resultssupporting
confidence: 57%
“…Previous studies indicated that 4PMO appears solely in 3(H) (I) in polar solutions and in crystalline. 3(H) (I) was determined to be predominant in liquid phase by ab initio calculation, rotational spectroscopy and matrix‐isolation infrared (IR) spectroscopy . Matrix‐isolation IR experiments further revealed that hydroxyl (II) can be formed via photoisomerization channel upon ultraviolet (UV) irradiation of 3(H) (I) …”
Section: Introductionmentioning
confidence: 99%
“…Der Prototyp für diese Art von Gleichgewicht ist das System 2‐Hydroxypyridin/2‐Pyridinon, wobei die OH‐Form um 3.2(4) kJ mol −1 stabiler ist 23. Im System 4‐Hydroxypyrimidin/4‐Pyrimidinon ist hingegen die Ketoform um 2.0(9) kJ mol −1 günstiger, was bedeutet, dass die Einführung einer zweiten N/NH‐Gruppe in den aromatischen Ring die Ketoform stabiler macht 24. Das Vorhandensein einer zusätzlichen C Ring ‐OH/CO‐Gruppe im Uracilring steigert die Stabilität der Ketoform so weit, dass im MW‐Spektrum ausschließlich die Diketoform nachweisbar ist 25…”
Section: Methodsunclassified
“…However, the ground state enol–keto tautomerization between OHP and NHP in gas phase is practically prohibited because of very large transition barrier (34–38 kcal mol −1 ) . Increasing the number of OH groups attached to aromatic, heterocyclic rings, and the number of N atoms in the ring significantly shift the tautomeric equilibrium toward the keto forms, as going from 2‐OH pyridine to 4‐OH pyrimidine and to uracil …”
Section: Introductionmentioning
confidence: 99%